Simulating academic writing: Didactic assumptions and problems in teaching and following academic text procedures - ILUK, JAN (Glottodidactica, 2021)
The preparation of a written diploma work is often a prerequisite for completion of one’s academic studies. The requirements that it must comply with, require targeted and systematic instruction in developing academic writing skills. This article introduces the concept of academic writing and effects of developing it, based on the simulation of the editing processes of a scholarly text.